Mutating Ecologies in Contemporary Art - Alonso, Christian (Col·lecció AGI (Art, Globalization, Interculturality), 2019)
What role might art exert in light of the challenges posed by climate change, resource depletion, and the diverse political and cultural crises our societies face in the twenty-first century? The hypothesis guiding this book is born of Félix Guattari's claim that in confronting the multi-faceted problems of our global political economy we need to develop a more complex analysis of nature, culture and technology, shifting from catastrophic, end-of-the world narratives to productive, generative, trans-species alliances for the sake of the sustainability of life on the planet. Because capitalism is no longer understood merely as a mode of production but as a system of semiotization, homogenization, and of transmission of forms of power over goods, labour and individuals, only the emergence of other relational subjective formations would be able to counteract the fixation of desire towards capital and its diverse crystallizations of power. New social practices, new aesthetic practices and new practices of the self in relation to the other are summoned to undertake an ethical-political reinvention of life. As Guattari argues, it is about reappropiating universes of value and paving the way for the emergence of processes of singularization involving a mutating subjectivity, a mutating socius, and a mutating environment. This book is engaged in thinking about the conjunction of the ecological turn in contemporary art and the attention given to matter in recent humanist scholarship as a way of exploring how new configurations of the world suggest new ways of being and acting in that world. Contributors investigate the means by which art can act as an existential catalysist, providing ways of changing our modes of relation beyond traditional modes of representation and, in doing so, instituting transformation.